Gain-of-function variants identified in vigabatrin-hypersensitive epileptic encephalopathies. - Absalom, Nathan L; Liao, Vivian W Y; Kothur, Kavitha; Indurthi, Dinesh C; Bennetts, Bruce; Troedson, Christopher; Mohammad, Shekeeb S; Gupta, Sachin; McGregor, Iain S; Bowen, Michael T; Lederer, Damien; Mary, Sandrine; et al. (Brain Commun, 2020)
Variants in the gene encoding the β3-subunit of the γ-aminobutyric acid type A ( receptor are associated with various developmental and epileptic encephalopathies. Typically, these variants cause a loss-of-function molecular phenotype whereby γ-aminobutyric acid has reduced inhibitory effectiveness leading to seizures. Drugs that potentiate inhibitory GABAergic activity, such as nitrazepam, phenobarbital or vigabatrin, are expected to compensate for this and thereby reduce seizure frequency. However, vigabatrin, a drug that inhibits γ-aminobutyric acid transaminase to increase tonic γ-aminobutyric acid currents, has mixed success in treating seizures in patients with variants: some patients experience seizure cessation, but there is hypersensitivity in some patients associated with hypotonia, sedation and respiratory suppression. A variant that responds well to vigabatrin involves a truncation variant (p.Arg194*) resulting in a clear loss-of-function. We hypothesized that patients with a hypersensitive response to vigabatrin may exhibit a different γ-aminobutyric acid A receptor phenotype. To test this hypothesis, we evaluated the phenotype of variants in (p.Glu77Lys and p.Thr287Ile) associated with patients who are clinically hypersensitive to vigabatrin. We introduced the p.Glu77Lys and p.Thr287Ile variants into a concatenated synaptic and extrasynaptic γ-aminobutyric acid A receptor construct, to resemble the γ-aminobutyric acid A receptor expression by a patient heterozygous for the variant. The mRNA of these constructs was injected into oocytes and activation properties of each receptor measured by two-electrode voltage clamp electrophysiology. Results showed an atypical gain-of-function molecular phenotype in the p.Glu77Lys and p.Thr287Ile variants characterized by increased potency of γ-aminobutyric acid A without change to the estimated maximum open channel probability, deactivation kinetics or absolute currents. Modelling of the activation properties of the receptors indicated that either variant caused increased chloride flux in response to low concentrations of γ-aminobutyric acid that mediate tonic currents. We therefore propose that the hypersensitivity reaction to vigabatrin is a result of variants that exacerbate GABAergic tonic currents and caution is required when prescribing vigabatrin. In contrast, drug strategies increasing tonic currents in loss-of-function variants are likely to be a safe and effective therapy. This study demonstrates that functional genomics can explain beneficial and adverse anti-epileptic drug effects, and propose that vigabatrin should be considered in patients with clear loss-of-function variants.

Complex Compound Inheritance of Lethal Lung Developmental Disorders Due to Disruption of the TBX-FGF Pathway. - Karolak, Justyna A; Vincent, Marie; Deutsch, Gail; Gambin, Tomasz; Cogné, Benjamin; Pichon, Olivier; Vetrini, Francesco; Mefford, Heather C; Dines, Jennifer N; Golden-Grant, Katie; Dipple, Katrina; Freed, Amanda S; et al. (Am J Hum Genet, 2019)
Primary defects in lung branching morphogenesis, resulting in neonatal lethal pulmonary hypoplasias, are incompletely understood. To elucidate the pathogenetics of human lung development, we studied a unique collection of samples obtained from deceased individuals with clinically and histopathologically diagnosed interstitial neonatal lung disorders: acinar dysplasia (n = 14), congenital alveolar dysplasia (n = 2), and other lethal lung hypoplasias (n = 10). We identified rare heterozygous copy-number variant deletions or single-nucleotide variants (SNVs) involving TBX4 (n = 8 and n = 2, respectively) or FGF10 (n = 2 and n = 2, respectively) in 16/26 (61%) individuals. In addition to TBX4, the overlapping ∼2 Mb recurrent and nonrecurrent deletions at 17q23.1q23.2 identified in seven individuals with lung hypoplasia also remove a lung-specific enhancer region. Individuals with coding variants involving either TBX4 or FGF10 also harbored at least one non-coding SNV in the predicted lung-specific enhancer region, which was absent in 13 control individuals with the overlapping deletions but without any structural lung anomalies. The occurrence of rare coding variants involving TBX4 or FGF10 with the putative hypomorphic non-coding SNVs implies a complex compound inheritance of these pulmonary hypoplasias. Moreover, they support the importance of TBX4-FGF10-FGFR2 epithelial-mesenchymal signaling in human lung organogenesis and help to explain the histopathological continuum observed in these rare lethal developmental disorders of the lung.
Keywords: DNA Copy Number Variations; Female; Fibroblast Growth Factor 10; Gene Expression Regulation; Gestational Age; Humans; Infant, Newborn; Infant, Newborn, Diseases; Lung; Lung Diseases; Male; Maternal Inheritance; Organogenesis; Paternal Inheritance; Pedigree; Polymorphism, Single Nucleotide; Receptor, Fibroblast Growth Factor, Type 2; Signal Transduction; T-Box Domain Proteins

Whole-exome sequencing identifies novel variants in PNPT1 causing oxidative phosphorylation defects and severe multisystem disease. - Alodaib, Ahmad; Sobreira, Nara; Gold, Wendy A; Riley, Lisa G; Van Bergen, Nicole J; Wilson, Meredith J; Bennetts, Bruce; Thorburn, David R; Boehm, Corinne; Christodoulou, John (Eur J Hum Genet, 2016)
Recent advances in next-generation sequencing strategies have led to the discovery of many novel disease genes. We describe here a non-consanguineous family with two affected boys presenting with early onset of severe axonal neuropathy, optic atrophy, intellectual disability, auditory neuropathy and chronic respiratory and gut disturbances. Whole-exome sequencing (WES) was performed on all family members and we identified compound heterozygous variants (c.[760C>A];[1528G>C];p.[(Gln254Lys);(Ala510Pro)] in the polyribonucleotide nucleotidyltransferase 1 (PNPT1) gene in both affected individuals. PNPT1 encodes the polynucleotide phosphorylase (PNPase) protein, which is involved in the transport of small RNAs into the mitochondria. These RNAs are involved in the mitochondrial translation machinery, responsible for the synthesis of mitochondrially encoded subunits of the oxidative phosphorylation (OXPHOS) complexes. Both PNPT1 variants are within highly conserved regions and predicted to be damaging. These variants resulted in quaternary defects in the PNPase protein and a clear reduction in protein and mRNA expression of PNPT1 in patient fibroblasts compared with control cells. Protein analysis of the OXPHOS complexes showed a significant reduction in complex I (CI), complex III (CIII) and complex IV (CIV). Enzyme activity of CI and CIV was clearly reduced in patient fibroblasts compared with controls along with a 33% reduction in total mitochondrial protein synthesis. In vitro rescue experiments, using exogenous expression of wild-type PNPT1 in patient fibroblasts, ameliorated the deficiencies in the OXPHOS complex protein expression, supporting the likely pathogenicity of these variants and the importance of WES in efficiently identifying rare genetic disease genes.
Keywords: Axons; Exome; Exoribonucleases; High-Throughput Nucleotide Sequencing; Humans; Intellectual Disability; Male; Mitochondria; Mutation; Optic Atrophy; Oxidative Phosphorylation; Pedigree; Protein Structure, Quaternary